(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
In soils organic matter and clay minerals are often so associated that it is not clear that how the presence of organic matter influences the sorptive process of clay minerals. Â So, in order to factor and quantify component contributions of mineral fractions and humic acid phase to the sorption of pesticides on clay minerals, adsorption and desorption of three carbamate pesticides oxamyl (I), S-Ethyl-N-(methyl carbamoyl)-oxythio acetimidate (II) and N-Phenyl (ethyl cabamoyl) propylcarbamate (III) by Na+, Ca2+ saturated illite, kaolinite and humic acid-clay complexes were investigated by batch experiments. The adsorption was more on illite than kaolinite and followed the order pesticide III > I > II, adsorption on Na-saturated clay samples was more than Ca-saturated. The presence of humic acid enhances the pesticide adsorption. A composite model for estimating pesticide adsorption, which assumes mineral and organic matter fraction individually as adsorbent phases, predicted sorption within a factor of 0.75-1.4 times the measured value. The desorption data indicated that humic acid retains more pesticide than clay mineral. XRD patterns showed that humic acid is restricted to the external surfaces of clay tactoids, denoting that clay mineral fractions in soils including those with organic coatings play an important role in the retention of polar carbamate pesticides.